The state of our rivers: back to basics - Zainudin, Zaki (Enviromental Management and Research Association of Malaysia (ENSEARCH), 2011)
ssues pertaining to environmental awareness amongst the Malaysian public have gained tremendous ground in the past decade, with participation from the media, authorities and non-governmental organizations (NGOs ), pushing the subject matter forward. The exposure covers a wide array of topics in- cluding air, land and river pollution. However, for some of the younger generation, who were brought up in an urban setting, the meaning and importance of a clean river remains rather elusive. For most the part, urban river systems are polluted due to anthropogenic (man-made ) activities within a river ba- sin; take for example Sg. Galing Besar in the Sg. Kuantan basin, shown in Figure 1 below. The river has been channelized and is overwhelmed with various contaminants entering it. The high organic pollution level results in severe oxygen depletion, “choking ” aquatic species particularly those, which are more sensitive.